2010
DOI: 10.1136/emj.2009.074831
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department or general practitioner following transient ischaemic attack? A comparison of patient behaviour and speed of assessment in England and Canada

Abstract: Most patients presenting to an ED go urgently, whereas most going to a GP delay, particularly at weekends. Most Canadian patients, particularly those at high risk, go to an ED whereas most UK patients go to a GP. One way to reduce delay, particularly in the UK, would be to direct all patients with TIA to go to an ED rather than to their GP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…8 Similarly, the percentage of UK and Canadian patients who presented within 24 hours of a TIA was higher with events that occurred during the week rather than at the weekend. 33 Although the current study found no association of a previous personal history of stroke or TIA with STAT score, this is consistent with the finding of Lasserson et al 8 in the UK that there was no difference in delay to healthcare help between patients with a first ever incident event and patients with recurrent events. The current study's findings of an association of higher STAT scores with older age and ATSI status are at odds with previous lack of evidence of association.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
“…8 Similarly, the percentage of UK and Canadian patients who presented within 24 hours of a TIA was higher with events that occurred during the week rather than at the weekend. 33 Although the current study found no association of a previous personal history of stroke or TIA with STAT score, this is consistent with the finding of Lasserson et al 8 in the UK that there was no difference in delay to healthcare help between patients with a first ever incident event and patients with recurrent events. The current study's findings of an association of higher STAT scores with older age and ATSI status are at odds with previous lack of evidence of association.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
“…The results of our study are consistent with those of previous studies. 3,5,8 Two reports using data from the Oxford Vascular Study 3,5 demonstrated that patients with motor weakness, speech disturbance, and symptom duration >60 minutes were less likely than other patients to delay in seeking medical attention. Patients with a higher predicted stroke risk were more likely to act quickly due apparently to the influence of weakness and prolonged symptom duration on behavior, although there was no association between the recognition of symptoms and the urgency of action.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential increase in stroke burden, and the likely underestimation of incidence rates, a significant amount of research has been conducted into TIA and minor stroke with a focus on risk, incidence and intervention. However, this research has predominantly used quantitative research methodologies in several key areas including patient decisions to seek help (Faiz, Sundseth, Thommessen, & Ronning, ; Geffner, Soriano, Perez, Vilar, & Rodriguez, ; Giles, Flossman, & Rothwell, ; Lasserson, Chandratheva, Giles, Mant, & Rothwell, ; Manawadu, Shuaib, & Collas, ), appropriate models of care and management (Ahmad et al., ; Jakel et al., ; Stead et al., ; Torres Macho et al., ), and outcome measures such as quality of life and depression (Luijendijk et al., ; Muus, Petzold, & Ringsberg, ; Shi et al., ).…”
Section: Introductionmentioning
confidence: 99%